Distribusi Kecakapan Abad 21 Siswa SMK di Indonesia - Amiruddin Amiruddin; Andi Muhammad Irfan; Muhammad Hasim S; Wirawan Setialaksana (Seminar Nasional LP2M UNM, 2021)
Abstract. The 21st Century literacy are skills that have to be mastered by students, especially high school vocational students. Some of these skills are conventional, numeracy, scientific, ICT and financial literacy. Identifying the literacy mastery among students is the stepping stone to prepare high school vocational students in facing the 4.0 era. The current research is an assosiative quantitative research which aim to investigate: 1) the distribution of the literacy mastery among high school vocational students, 2) the association of the literacy mastery with student grades and their school regional, and the distribution of the parts of the literasy among students in vocational school in Indonesia. The current research is taken place in all vocational school in South and West Sulawesi. The research instrument are questionnaire which results will be analysed using Chi-Square Test. The results show that 1) 86.7% students of vocational school show a good understanding about the literacy, 2) the literacy are not associate with student grade and school regional and 3) most of students of vocational school shows a good understanding about the literacy, but the numeracy and financial literacy of the students are relatively in low category.Keywords: 21st Century literacy, Vocational School